A decade of CO2 flux measured by the eddy covariance method including the COVID-19 pandemic period in an urban center in Sakai, Japan. (1st July 2022) - Ueyama, Masahito; Takano, Tsugumi
Abstract: Cities constitute an important source of greenhouse gases, but few results originating from long-term, direct CO2 emission monitoring efforts have been reported. In this study, CO2 emissions were quasi-continuously measured in an urban center in Sakai, Osaka, Japan by the eddy covariance method from 2010 to 2021. Long-term CO2 emissions reached 22.2 ± 2.0 kg CO2 m −2 yr −1 from 2010 to 2019 (± denotes the standard deviation) in the western sector from the tower representing the densely built-up area. Throughout the decade, the annual CO2 emissions remained stable. According to an emission inventory, traffic emissions represented the major source of CO2 emissions within the flux footprint. The interannual variations in the annual CO2 flux were positively correlated with the mean annual traffic counts at two highway entrances and exits. The CO2 emissions decreased suddenly, by 32% ± 3.1%, in April and May 2020 during the period in which the first state of emergency associated with COVID-19 was declared. The annual CO2 emissions also decreased by 25% ± 3.1% in 2020. Direct long-term observations of CO2 emissions comprise a useful tool to monitor future emission reductions and sudden disruptions in emissions, such as those beginning in 2020 during the COVID-19 pandemic. Graphical abstract: Image 1 Highlights: The urban center in Sakai, Japan, was a net source of CO2 on multiple timescales. The annual CO2 emissions remained stable from 2010 to 2019. Interannual variations in the CO2 emission were correlated with traffic counts. The annual CO2 emissions decreased by 25% in 2020 associated with COVID-19. Inventory suggests traffic CO2 emissions contributed to 60% of the total emissions.